IMPLEMENTASI SUPERVISI AKADEMIK KEPALA SEKOLAH DI SMA NEGERI I KOTA LUBUKLINGGAU - Eva Gusseventini; Rohiat Rohiat; Puspa Djuwita (UNIVERSITAS BENGKULU, 2017)
The objective of this research is to describe how the academic supervision of the headmaster in Senior High School number 1 Lubuklinggau. The specific problems of this research consisted of several questions, how the academic supervision of headmaster in planning, process, evaluation, and the follow up. This study used the qualitative descriptive method. The technique for collecting the data is done by interview, observation, and documentation. The result of this study showed that the headmaster had done the academic supervision to the teachers by using clinical method by holding class visit, the follow up of the supervision is with make a lesson teacher team for sharing about the teachers documents and how to manage the class better.